KEMAMPUAN PENALARAN ILMIAH SISWA SMA DALAM PEMBELAJARAN FISIKA MENGGUNAKAN MODEL INKUIRI TERBIMBING DISERTAI DIAGRAM BERPIKIR MULTIDIMENSI - Fiska Anjani; Supeno Supeno; Subiki Subiki (Lantanida Journal, 2020)
Scientific reasoning is an ability to argue the concept of knowledge using scientific principles to build a deep understanding. Scientific reasoning is one of the essential skills in the 21st century as a provision in facing global challenges. Scientific reasoning is also one of the skills needed in learning physics because, in essence, physics learning requires a deep understanding of concepts. The fact shows that the scientific reasoning skills of students are still low. Students tend to solve problems without recognizing ideas and have a tendency to plug and chug as much as they remember, so learning is needed that can improve scientific reasoning skills. This scientific reasoning skill can be applied by combining guided inquiry learning models with multidimensional thinking diagram aids that are packaged in the form of student worksheets. Implementing the guided inquiry learning model will help students in the reasoning process because each process directs students to follow several methods and practices that are similar to scientists in building knowledge. Multidimensional thinking diagrams can help students in each inquiry process and assist students in analyzing and solving problems. Guided inquiry accompanied by multidimensional thinking diagrams can improve scientific reasoning skills.